(untitled) - Goodner, David; Tsurumi, Andrea (New York, 2020)
"Kondo is big. Kezumi is little. They lived on an island with fruit trees and berry bushes and flitter-birds and fluffle-bunnies. When a surprise bottle washes ashore, they discover a map with a mysterious message: WE ARE NOT ALONE. Kezumi wants to follow the map and explore the world. Kondo wants to stay home and pick fruit from the fruit tree and berries from the berry bushes. But once Kezumi builds the perfect boat, the best friends set sail together to see...well, they don't know!"--
Keywords: Fiction; Best friends; Fiction; Juvenile fiction; Fiction; Islands; Friendship; Fiction; Best friends; Juvenile fiction; Friendship; Juvenile fiction; Islands; Juvenile fiction; Adventure and adventurers; Adventure and adventurers; Sea fiction; Action and adventure fiction